2013
DOI: 10.1152/ajpcell.00303.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NSAIDs on Na+/H+ exchanger activity in rat colonic crypts

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs; 1) are widely recommended for several acute and chronic conditions. For example, both indomethacin and aspirin are taken for pain relief. Aspirin is also used for prevention of myocardial infarction, and indomethacin can be administered orally or as a suppository for patients with rheumatoid disease and other chronic inflammatory states. However, use of NSAIDs can cause damage to the mucosal barrier surrounding the gastrointestinal (GI) tract, increasing the risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
(72 reference statements)
0
9
1
Order By: Relevance
“…The present study confirms this finding, as the SLC9a2 gene was found highly expressed compared to dura. The blocking effect of amiloride on this particular transporter is well known, but lately it has also been demonstrated that several non-steroid anti-inflammatory drugs (NSAIDs) also interact and block the transporter (23), which may in fact account for the well-known side effects of many NSAIDs, including tinnitus, dizziness, and imbalance. Accordingly, the present data supports a cautious approach when administering both amiloride and NSAIDs in patients with Ménière's disease.…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirms this finding, as the SLC9a2 gene was found highly expressed compared to dura. The blocking effect of amiloride on this particular transporter is well known, but lately it has also been demonstrated that several non-steroid anti-inflammatory drugs (NSAIDs) also interact and block the transporter (23), which may in fact account for the well-known side effects of many NSAIDs, including tinnitus, dizziness, and imbalance. Accordingly, the present data supports a cautious approach when administering both amiloride and NSAIDs in patients with Ménière's disease.…”
Section: Discussionmentioning
confidence: 99%
“…The colon was then removed and flushed with 4°C cold HEPES Ringer solution (See Table 1) to remove the residual fecal material from the interior of the colon as previously described [20]. Briefly, we cut the clean distal colon into two longitudinal strips [21, 22]. The two strips were then immersed into a digestion solution that was composed of a low Calcium High EDTA/HEPES buffer.…”
Section: Methodsmentioning
confidence: 99%
“…We then transfer a 200 µL aliquot of the crypts HEPES solution to the chamber, then incubated the crypts with a 1 µL of BCECF/AM dye (Santa Cruz Biotechnology) a pH sensitive dye as previously described [22, 24]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indomethacin, a highly potent nonsteroidal anti-inflammatory drug with nonselective inhibition on cyclooxygenases (5) is known to possess both prominent anti-inflammatory and analgesic-antipyretic properties (12). The clinical use of indomethacin has been effectively used in various clinic conditions, such as several acute and chronic pains (40), rheumatoid arthritis (45) and ocular inflammation (19). Apart from the potent inhibition on cyclooxygenases, the anti-inflammatory and analgesic effects of indomethacin is also achieved through a variety of mechanisms, including regulation of NHE (40) and Cl -/HCO 3 ion transporter (48).…”
Section: Introductionmentioning
confidence: 99%